A Novel Tool for the Identification and Characterization of Repetitive Patterns in High-Density Contact Mapping of Atrial Fibrillation - Zeemering, Stef; van Hunnik, Arne; van Rosmalen, Frank; Bonizzi, Pietro; Scaf, Billy; Delhaas, Tammo; Verheule, Sander; Schotten, Ulrich (Frontiers in Physiology, 2020)
Introduction Electrical contact mapping provides a detailed view of conduction patterns in the atria during atrial fibrillation (AF). Identification of repetitive wave front propagation mechanisms potentially initiating or sustaining AF might provide more insights into temporal and spatial distribution of candidate AF mechanism and identify targets for catheter ablation. We developed a novel tool based on recurrence plots to automatically identify and characterize repetitive conduction patterns in high-density contact mapping of AF. Methods Repetitive conduction patterns recorded by a multi-electrode array were detected and visualized using recurrence plots. Recurrence plots were constructed by first transforming atrial electrograms to activation-phase signals and then quantifying the degree of similarity between snapshots of the activation-phase in the electrode array. An AF cycle length dependent recurrence threshold was applied to discriminate between repetitive and non-repetitive snapshots. Intervals containing repetitive conduction patterns were delineated by an algorithm that locates square blocks in a recurrence plot with a high recurrence rate. Intervals that contained repetitive patterns representing similar patterns were then grouped into clusters. To demonstrate the ability to detect and quantify the incidence, duration and size of repetitive patterns, the tool was applied to left and right atrial recordings in a goat model of different duration of persistent AF (3 weeks AF (3wkAF, n=8) and 22 weeks AF (22wkAF, n=8)), using a 249-electrode mapping array (2.4mm inter-electrode distance). Results Recurrence plots identified frequent recurrences of activation patterns in all recordings and indicated a strong correlation between recurrence plot threshold and AF cycle length. Prolonged AF duration was associated with shorter repetitive pattern duration (mean maximum duration 3wkAF: 74 cycles, 95% confidence interval [54-94] vs. 22wkAF: 41 cycles [21-62], p=0.03), and smaller recurrent regions within repetitive patterns (3wkAF 1.7cm2 [1.0-2.3] vs. 22wkAF 0.5cm2 [0.0-1.2], p=0.02). Both breakthrough patterns and re-entry were identified as repetitive conduction patterns. Conclusions Recurrence plots provide a novel way to delineate high-density contact mapping of atrial fibrillation. Dominant repetitive conduction patterns were identified in a goat model of sustained AF. Application of the developed methodology using the new generation of multi-electrode catheters could identify additional targets for catheter ablation of AF.